MILITARY-PATRIOTIC EDUCATION AND ITS ROLE IN YOUTH DEVELOPMENT - Valixanov Ilyos Ilxamovich (Modern American Journals, 2026)
This article analyzes the theoretical foundations, goals and objectives, principles, as well as pedagogical and psychological mechanisms of educating youth in the spirit of military patriotism. Military-patriotic education is a process of forming in the younger generation a sense of loyalty to the Motherland, national pride, civic responsibility, constitutional duty, and readiness for military service. The study scientifically substantiates the essence and content of the concept of patriotism, as well as its organic connection with national values, historical heritage, and universal human principles. The article is based on the legislative documents of the Republic of Uzbekistan in the field of education and youth policy and draws upon scholarly research devoted to the ideology of national independence and youth upbringing.
Keywords: National development, Patriotic education, Youth upbringing, National values, Family and community (mahalla), Sense of Motherland, Digital technologies, Civic responsibility.